The Otway shallow fault experiment: Insights from surface monitoring - Claire Patterson; Andrew Zammit-Mangion; Ziqiu Xue; Kexin Zhang; Zibo Zhou; Wendy Timms; Andrew J. Feitz (International Journal of Greenhouse Gas Control, 2026)

Hybrid machine learning for predicting groundwater level: A comparison of boosting algorithms with neural networks - Milad Barzegar; Saba Gharehdash; Faysal Chowdhury; Ming Liu; Wendy Timms (Groundwater for Sustainable Development, 2025)

Optimising soil gas monitoring at an on-shore geological carbon sequestration site - Kexin Zhang; Svetlana Stevanovic; William Howcroft; Wendy Timms (International Journal of Greenhouse Gas Control, 2025)

Evaluating the influence of carbon quantum dots on starch-based bioplastics: Toward potential food packaging applications - Shima Jafarzadeh; Mitra Golgoli; Zeinab Qazanfarzadeh; Mehrdad Forough; Peng Wu; Wendy Timms; Colin J. Barrow; Minoo Naebe; Masoumeh Zargar (Food Packaging and Shelf Life, 2025)

Hydrogeological implications of fault-related folding in a Triassic braided sandstone - Timothy C. McMillan; Titus Murray; Martin S. Andersen; Wendy A. Timms; Gabriel C. Rau (Journal of Structural Geology, 2025)

Shallow groundwater near a deep-well CO2 storage site—15 years of stable water quality for agricultural use - Zibo Zhou; Kexin Zhang; Damien L. Callahan; Wendy Timms (Environmental Science and Pollution Research, 2025)
Injecting CO 2 into deep geological formations can be an effective carbon removal and storage technology to mitigate global climate change. Interaction of injected CO 2 with rock formations changes pH and hydrochemistry within the deep injection zone (> 800 m depth). However, cap rocks and multiple tight aquitards typically act as barriers to protect the shallow aquifer from changes in the injection zone. Monitoring and evaluation of shallow groundwater quality are essential to verify that carbon capture storage projects (CCS) do not impact the near-surface environment. This study investigated shallow groundwater quality using long-term data (2006–2023) from a regular monitoring program at the Otway International Test Centre (OITC) in Victoria, Australia. It was found that shallow groundwater quality was stable over at least 15 years, during which time three phases of CO 2 injection into a deep storage zone occurred. The results highlighted groundwater quality complied with guidelines of Food and Agriculture Organization (FAO) and Australian water quality guidelines. Minor and localised changes observed in salinity or pH in shallow monitoring piezometers were caused by natural processes. Moreover, a wide range of groundwater quality indicators were evaluated. The results demonstrated that the groundwater quality of shallow aquifers (< 80 m) at OITC is suitable for agriculture. The study provides assurance and confidence to stakeholders that the quality of the near-surface environment has not been impacted by CO 2 injection into confined formations and no pollution has been detected. Although numerous CCS sites around the world are subject to monitoring, no evidence of changes in shallow groundwater quality has been reported that could be traced to CO 2 injection in confined formations at > 800 m depth.

Comprehensive life cycle assessment of garden organic waste valorisation: A case study in regional Australia - Sirjana Adhikari; M.A. Parvez Mahmud; Ellen Moon; Wendy Timms (Journal of Cleaner Production, 2024)

Comparative analysis of biochar carbon stability methods and implications for carbon credits - Sirjana Adhikari; Ellen Moon; Jorge Paz-Ferreiro; Wendy Timms (Science of The Total Environment, 2024)

Identifying biochar production variables to maximise exchangeable cations and increase nutrient availability in soils - Sirjana Adhikari; Ellen Moon; Wendy Timms (Journal of Cleaner Production, 2024)

Evaluating fundamental biochar properties in relation to water holding capacity - Sirjana Adhikari; M.A. Parvez Mahmud; Minh Duc Nguyen; Wendy Timms (Chemosphere, 2023)

Multifactor analysis of specific storage estimates and implications for transient groundwater modelling - Faysal Chowdhury; Jinzhe Gong; Gabriel C. Rau; Wendy A. Timms (Hydrogeology Journal, 2022)
Specific storage ( S S ) has considerable predictive importance in the modelling of groundwater systems, yet little is known about its statistical distribution and dependency on other hydrogeological characteristics. This study provides a comprehensive overview and compiles 430 values of S S from 183 individual studies, along with complementary hydrogeological information such as estimation methods, lithology, porosity, and formation compressibility. Further evaluation of different approaches to determine and utilize S S values for numerical groundwater modelling, along with the scale and source of uncertainty of different measurement methods, was carried out. Overall, S S values range across six orders of magnitude (from 3.2 × 10 –9 to 6 × 10 –3 m –1 ) with a geometric mean of 1.1 × 10 –5 m –1 and the majority (> 67%) of values are in the order of 10 –5 and 10 –6 m –1 . High S S values of ~10 –4 m –1 were reported for glacial till and sandy lithologies, particularly for shallow and thin strata where leakage may obscure the estimation of S S . A parallel assessment of 45 transient regional-scale groundwater models reveals a disconnect between findings of this study and the way S S is treated in practice, and that there is a lack of foundational S S data to conduct quantitative uncertainty analysis. This study provides the first probability density functions of S S for a variety of lithology types based on the field and laboratory tests collated from the literature. Log transformed S S values follow a Gaussian/normal distribution which can be applied to evaluate uncertainties of modelling results and therefore enhance confidence in the groundwater models that support decision making.

Selecting Environmental Water Tracers to Understand Groundwater around Mines: Opportunities and Limitations - Devmi Kurukulasuriya; William Howcroft; Ellen Moon; Karina Meredith; Wendy Timms (Mine Water and the Environment, 2022)
Underground mining operations have the potential to alter groundwater systems and facilitate hydraulic connections between surface water and groundwater. The nature and degree of these interactions need to be evaluated to identify mining risks to surrounding water resources and to predict potential operational effects and environmental impacts, such as hydraulic stress on local surface waters. Environmental water tracers (EWTs) are commonly used to study such interactions in mine water and hydrogeological studies. However, the opportunities presented by EWTs could be more widely utilised to benefit the mining industry and the environment. Some of the challenges faced include the lack of practical frameworks, the need for more examples of EWTs applications in mining, and the possibility of complex interpretation of tracer results. This paper reviews previous studies that have applied EWTs in groundwater systems within or near mine sites, mostly from Australia, China, and India. The EWTs used in these studies include water quality parameters, major ions, stable isotopes, radioisotopes, and dissolved gases. The opportunities of applying multiple EWTs to identify water sources, mixing, and determine recharge rates and groundwater residence times are discussed. Limitations of different EWTs in terms of their capabilities, reliability, cost of analysis, effort, and processing times are reviewed. Steps for selecting suitable EWTs for specific mine hydrogeology assessments should be commensurate with the risks. Finally, this paper provides an overview of suitable EWTs that will be a useful contribution to appropriate water resource management decisions around mines.

Analytical methods to estimate the hydraulic conductivity of jointed rocks - Mahdi Zoorabadi; Serkan Saydam; Wendy Timms; Bruce Hebblewhite (Hydrogeology Journal, 2022)

Evaluation of Impact of Potential Extreme Rainfall Events on Mining in Peru - Francisco R. Gonzalez; Simit Raval; Ros Taplin; Wendy Timms; Michael Hitch (Natural Resources Research, 2019)

Establishing Empirical Relationships for the Effects of Water Content on the Mechanical Behavior of Gosford Sandstone - Hossein Masoumi; James Horne; Wendy Timms (Rock Mechanics and Rock Engineering, 2017)

Improved barometric and loading efficiency estimates using packers in monitoring wells - Scott B. Cook; Wendy A. Timms; Bryce F.J. Kelly; S. Lee Barbour (Hydrogeology Journal, 2017)

Mapping the hydraulic connection between a coalbed and adjacent aquifer: example of the coal-seam gas resource area, north Galilee Basin, Australia - Zhenjiao Jiang; Gregoire Mariethoz; Christoph Schrank; Malcolm Cox; Wendy Timms (Hydrogeology Journal, 2016)

Measuring dissolved organic carbon δ13C in freshwaters using total organic carbon cavity ring-down spectroscopy (TOC-CRDS) - Adam Hartland; Andy Baker; Wendy Timms; Yulia Shutova; Dorothy Yu (Environmental Chemistry Letters, 2012)

Hydrogeological investigation of mud-mound springs developed over a weathered basalt aquifer on the Liverpool Plains, New South Wales, Australia - R. Ian Acworth; Wendy A. Timms (Hydrogeology Journal, 2003)